Preparation method and application of cesium-based perovskite solution and film
By improving the preparation of cesium-based perovskite solution and two-step interdiffusion technology, the problems of incomplete reaction and consistency of perovskite solar cells were solved, efficient cesium-based titanium ore film preparation and high-efficiency battery efficiency were achieved, and the industrialization process of perovskite cells was promoted.
Patent Information
- Application Number
- CN202510619643.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-05-14
- Publication Date
- 2025-09-26
AI Technical Summary
Existing methods for preparing perovskite solar cells have problems such as incomplete reaction, poor consistency, use of toxic solvents, and inaccurate stoichiometry, which affect cell efficiency and industrialization progress.
Using efficient cesium-based perovskite solution preparation technology, cesium salt and metal halide powders are dissolved by oxidizing N-methylpyrrolidone and dimethyl sulfoxide, and a new two-step interdiffusion technology is used to extend the crystallization time, avoid the use of toxic solvents, and form high-quality films.
It has achieved efficient cesium-based perovskite film preparation, improved battery consistency and repeatability, and achieved a photoelectric conversion efficiency of 17.85%, providing a new path for the commercialization of perovskite batteries.
Smart Images

Figure CN120711981A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a cesium-based perovskite precursor solution, a preparation method of a cesium-based perovskite film and application of the same in a perovskite solar cell, and belongs to the field of photoelectric devices. Background Art
[0002] Solar energy is an inexhaustible source of clean energy. Since the discovery of the photovoltaic effect, solar cells have been the subject of extensive research. After decades of development, they have been successfully applied to both military and civilian fields, and their applications have been widely recognized in the past decade. Despite the remarkable success of solar cells, scientists continue to strive to reduce costs and improve photoelectric conversion efficiency.
[0003] In 2009, Japanese scientist Miyasaka and his team prepared the first organic-inorganic hybrid perovskite solar cell and achieved a photoelectric conversion efficiency of 3.8% (Journal of the American Chemical Society (JACS), 2009, 131 (17), 6050-6051). Due to its low raw material cost and high photoelectric conversion efficiency, it has become a research hotspot in the field of new energy. After more than ten years of development, it has made great progress, with a photoelectric conversion efficiency greater than 25% (Nature, 2021, 598 (7881), 444-450). In order to solve the attenuation characteristics of the photoelectric conversion efficiency of perovskite solar cells in the air, cesium doping is considered to be a very wise strategy, so the research on cesium-based perovskite solar cells has important scientific significance.
[0004] The preparation method of perovskite solar cells is generally divided into a two-step method and a one-step method, and the two-step method includes a two-step continuous immersion method and a two-step mutual diffusion method, and the one-step method includes a rapid crystallization antisolvent method, etc. (Nature Materials, 2020, 19 (6), 636-643); Nature, 2013, 499 (7458), 316-319 and Energy Environ Sci. 2014, 7, 2619-2623). Among these methods, the two-step mutual continuous immersion method causes incomplete reaction and poor consistency due to the concentration of the immersion solution changing with time and the density of the metal halide. The two-step mutual diffusion method causes incomplete reaction due to uneven and incomplete diffusion. The rapid crystallization antisolvent method uses the antisolvent chlorobenzene to quickly drip into the solution at the moment of supersaturation, taking away the excess organic solution, so that there is no pinhole-shaped defect on the surface of the perovskite film, but it has the disadvantages of a short supersaturation instantaneous time window (only 1-2 seconds) and chlorobenzene being a toxic solvent. In order to solve these problems, it is of great scientific significance to develop a new two-step mutual diffusion technology to prepare high-quality cesium-based perovskite films and solar cells. At the same time, due to the low stoichiometric amount of cesium doping and inaccurate weighing, the development of a cesium-based perovskite precursor solution preparation technology is also of great scientific significance. The patent for this invention is supported by the "14th Five-Year Plan" National Key R&D Program Project "Gradually Deep Impurity Removal of Rubidium and Cesium Salts and Preparation Technology of High-Purity Rubidium and Cesium Metals and Their Compounds" (2023YFC2908205). Summary of the Invention
[0005] The present invention discloses a method for preparing an efficient cesium-based perovskite solution, a film and a battery, and belongs to the field of optoelectronic devices. A technology for dissolving cesium salts is invented, namely, dissolving cesium salts and metal halide powders by oxidizing N-methylpyrrolidone (NMP) and a small amount of dimethyl sulfoxide (DMSO) additives, which solves the problems of poor solubility and complex preparation of cesium-based perovskite precursors. At the same time, the present invention also invented a technology for preparing high-quality cesium-based perovskite films, namely a new two-step mutual diffusion technology. It first spin-coats an excess of a mixture of metal halide and organic halide on the hole transport layer, and then vertically drips the organic halide solution, and forms a dense, high-quality film by heating and annealing. Compared with traditional technologies, the present invention prolongs the crystallization time, removes toxic chlorobenzene, and improves battery consistency. The cesium-based inverted pure iodine perovskite solar cell prepared based on the invention achieves a photoelectric efficiency of 17.85%, providing a new path for the commercialization of perovskite cells.
[0006] The specific steps are as follows:
[0007] A method for preparing a cesium-based perovskite precursor solution comprises the following steps:
[0008] (1) Using a balance, weigh the cesium salt and metal halide powders separately and then mix them to form a precursor powder;
[0009] (2) adding the first organic solvent to the mixture precursor powder of step (1), stirring the mixture with a magnetic stirrer for 6-8 hours until it is completely dissolved to form a first precursor solution;
[0010] (3) Weighing the organic halide and the metal halide separately using a balance, and then mixing them into a precursor powder;
[0011] (4) adding a second organic solvent to the mixture of step (3) and stirring with a magnetic stirrer until the mixture is completely dissolved to form a second precursor solution;
[0012] (5) filtering the first precursor solution and the second precursor solution in steps (2) and (4) respectively through an organic filter to remove insoluble impurities;
[0013] (6) Using a pipette, the first and second precursor solutions filtered in step (5) are extracted respectively in a certain volume ratio and mixed to form a third precursor solution, i.e., a cesium-based perovskite solution.
[0014] The cesium salt is one or more of CsCl, CsBr, CsI, and Cs2CO3.
[0015] The metal halide is PbCl2, PbBr2 or PbI2.
[0016] The organic halide is CH3NH3Cl, CH3NH3Br or CH3NH3I.
[0017] The first organic solvent is a mixture of NMP and DMSO.
[0018] Preferably, the volume ratio of NMP to DMSO is (5:1)-(3:1).
[0019] Preferably, the NMP is oxidized in air for 5-8 hours.
[0020] The second organic solvent is DMF and DMSO.
[0021] Preferably, the volume ratio of DMF to DMSO is (90-105):(1-10).
[0022] Preferably, the concentration of the first precursor is 1M to 2M.
[0023] Preferably, the concentration of the second precursor is 460 mg / ml to 700 mg / ml.
[0024] Preferably, the molar ratio of the cesium salt to the metal halide is 1:1.
[0025] Preferably, the molar ratio of the organic halide to the metal halide in step (3) is 1:4 to 1:3.
[0026] Preferably, the volume ratio of the first precursor solution to the second precursor solution in step (6) is (10-100):(800-1200).
[0027] The solid powders of the cesium salt and the metal halide are weighed in dry air, and the organic halide is weighed in a nitrogen environment.
[0028] In addition, the present invention uses a novel two-step interdiffusion technology to prepare a cesium-based perovskite film, which solves the technical problems of pinholes and unevenness in the perovskite film. At the same time, it solves the problem that the rapid crystallization anti-solvent method requires the use of toxic chlorobenzene as an extractant, prolongs the anti-solvent extraction time, and improves the battery consistency. The anti-solvent method chlorobenzene extraction time is only a short 1-2 seconds, which easily leads to discontinuity and many holes in the perovskite film, which is extremely unfavorable for industrial development. The specific steps are as follows:
[0029] (1) Adding an organic halide to a third organic solvent, stirring until completely dissolved, filtering with an organic filter head, and allowing to stand to form a fourth precursor solution.
[0030] (2) The third precursor mixed solution according to claim 1 is deposited on the surface of the substrate, and during the spin coating crystallization process, the fourth organic halide precursor solution is vertically inserted to form a perovskite wet film.
[0031] (3) Annealing the perovskite wet film at a temperature of 50 to 150° C. for 10 to 60 minutes to obtain a high-quality cesium-based perovskite film with good crystallization.
[0032] The third organic solvent in step (1) is isopropanol.
[0033] The concentration of the fourth precursor solution is 20 mg / ml-80 mg / ml.
[0034] In the step (2), the wet film is deposited by spin coating, the first spin coating speed is 6000-8000 rpm, the spin coating time is 20-60 seconds, the second spin coating speed is 4000-5999 rpm, and the spin coating time is 40-60 seconds.
[0035] Preferably, the time for vertically dripping the fourth precursor solution is 10-40 seconds in the reverse direction.
[0036] Furthermore, a novel two-step interdiffusion technique was used to prepare cesium-based perovskite thin films, ultimately leading to the fabrication of cesium-based perovskite solar cells. This technique achieved impressive photoelectric conversion efficiencies, overcoming the issues of toxic chlorobenzene as an extractant and cell reproducibility. This represents a significant milestone for the industrialization of perovskite solar cells. The specific steps involved in the fabrication of cesium-based perovskite solar cells are as follows: transparent conductive glass, with or without a modified layer, hole transport layer, cesium-based perovskite thin film active layer, with or without a modified layer, electron transport layer, passivation layer, and metal electrode.
[0037] Preferably, the electron transport layer is one or more of TiO2, SnO2, PCBM, ZnO, with a thickness of 10 to 100 nm. Preferably, the hole transport layer is Spiro-OMeTAD, PTAA, NiO x One of the above, with a thickness of 5 to 150 nm.
[0038] Compared with the prior art, the present invention has the following beneficial effects:
[0039] The present invention employs a method for independently preparing precursor solutions in separate steps, finding a novel solution formula for dissolving cesium-based perovskite powder. This method employs NMP oxidized for 5-8 hours combined with a small amount of DMSO as an additive, effectively resolving the difficulty in dissolving cesium-based perovskite powder. Furthermore, by preparing the cesium-based perovskite solution and metal halide and organic halide solutions in separate steps, it further addresses issues such as low cesium stoichiometry and inaccurate weighing. The high-concentration cesium-based perovskite precursor solution can be prepared once and then withdrawn for multiple uses, further eliminating the tediousness of preparing multiple cesium-based perovskite solutions.
[0040] This invention successfully fabricates pinhole-free, continuous, high-quality cesium-based perovskite films using a novel two-step interdiffusion technique. By applying a precursor solution of a metal oxide and an organic halide, with an excess of metal oxide, and then vertically dripping the organic halide at an appropriate time from the spin coating process during the spin coating process, combined with an annealing process, this technique overcomes the incomplete chemical reaction of the perovskite in the traditional two-step interdiffusion technique and the reliance on toxic chlorobenzene as an extractant for rapid crystallization antisolvents. This technique extends the extractant intervention time (only 1-2 seconds with the antisolvent method), improving the consistency and repeatability of perovskite solar cells.
[0041] Through the present invention, a cesium-based perovskite precursor solution was successfully prepared, a high-quality pinhole-free cesium-based perovskite film was successfully prepared, a cesium-based perovskite solar cell was successfully prepared, and an encouraging photoelectric conversion efficiency of 17.85% was achieved. BRIEF DESCRIPTION OF THE DRAWINGS
[0042] Figure 1 : is a schematic structural diagram of a solar cell device of the present invention.
[0043] 1 is transparent conductive glass, 2 is a modified layer, 3 is a hole transport layer, 4 is a cesium-based perovskite film active layer, 5 is a modified layer, 6 is an electron transport layer, 7 is a passivation layer, and 8 is a metal electrode.
[0044] Figure 2 : is the X-ray diffraction (XRD) pattern of the cesium-based perovskite thin film layer of the present invention.
[0045] Figure 3 : The cesium-based perovskite film PTAA / Cs x (CH3NH3) 1-x SEM image of PbI3 (x is approximately 0.018).
[0046] Figure 4 :It is the cesium-based perovskite film Al2O3 / PTAA / Cs x (CH3NH3) 1-x SEM image of PbI3 (x is approximately 0.018).
[0047] Figure 5 : is the current-voltage spectrum of the cesium-based perovskite solar cell of the present invention. DETAILED DESCRIPTION
[0048] The following is combined with Figure 1-5 , a specific embodiment of the present invention is described in detail, but the protection scope of the present invention is limited.
[0049] Example 1
[0050] The following embodiments and examples are provided to further illustrate the present invention, but are not intended to limit the scope of protection of the present invention.
[0051] Example 1: Cesium-based perovskite Cs x (CH3NH3) 1-x PbI3 (x is about 0.018) precursor solution, film and perovskite solar cell
[0052] Precursor solution preparation
[0053] 1. First precursor solution:
[0054] Weigh CsI and PbI2 powders in dry air, add a mixed solvent of NMP and DMSO (volume ratio 5:1) that has been pre-oxidized for 6 hours to a concentration of 1 M, and after sufficient dissolution, filter with an organic filter to remove impurities.
[0055] 2. Second precursor solution:
[0056] Weigh CH3NH3I and PbI2 powders (molar ratio of 1:4) in a nitrogen environment and dissolve them in
[0057] DMF:DMSO (500:40) mixed solvent was used to make the concentration 556 mg / ml. After it was fully dissolved, it was filtered through an organic filter head and allowed to stand for 5 minutes.
[0058] 3. The third precursor solution:
[0059] The first and second precursor solutions were mixed at a volume ratio of 22.5:1000, stirred for 10 minutes, and allowed to stand for 5 minutes.
[0060] Preparation of cesium-based perovskite thin films
[0061] 1. Dissolve CH3NH3I in isopropanol (40 mg / ml) to form a fourth precursor solution.
[0062] 2. Spin-coat the third precursor solution onto the ITO substrate at a first speed of 6050 rpm for 21 seconds, a second speed of 4050 rpm for 42 seconds, and vertically add the fourth solution at the 37th second before the end. Anneal at 100°C for 35 minutes. Figure 2 This is the X-ray diffraction (XRD) pattern of the cesium-based perovskite film, where the red curve represents Al2O3 / PTAA / Cs x (CH3NH3) 1-x XRD pattern of PbI3, the black curve represents PTAA / Cs x (CH3NH3) 1-x XRD pattern of PbI3. As can be seen from the figure, the cesium-based perovskite film has good crystallinity and sharp diffraction peaks at 13.9 0 The strongest diffraction peak appears at the place where the (110) crystal plane appears. The angles of the diffraction peak sub-intensity are 28.3 0 ,32.4 0 ,19.8 0 , corresponding to crystal planes (220), (222) and (112). Comparing the red and black curves, the diffraction peak angles and crystallinity are very similar, which suggests that Al2O3 has no effect on the crystallization of cesium-based perovskite. Figure 3 Cesium-based perovskite films Cs grown on PTAA films were demonstrated x (CH3NH3) 1-x Scanning electron microscopy (SEM) image of PbI3. Figure 4 Cesium-based perovskite films Cs grown on Al2O3 / PTAA films were demonstrated. x (CH3NH3) 1- xSEM image of PbI3. The 20,000-fold magnified SEM image reveals that the surface morphologies of the two films are very similar, with uniform, smooth, and void-free surface crystals. Typically, perovskites exhibit pinhole-like pores on their surface. This demonstrates the superior technical advantages of this preparation method. This is consistent with the XRD data, and multiple characterization methods demonstrate the superior quality of the cesium-based perovskite films prepared using this technical solution. High-quality perovskite films are more conducive to the preparation of high-quality solar cells.
[0063] Preparation of cesium-based perovskite solar cells
[0064] The structure is ITO / Al2O3 / PTAA / cesium-based perovskite film / PEAI / PCBM / BCP / Ag. Figure 1 Device structure, 1 is ITO glass, 2 is Al2O3 nanoparticles, 3 is PTAA, 4 is Cs x (CH3NH3) 1-x PbI3 perovskite film, 5 is PEAI, 6 is PCBM, and 7 is Ag. Figure 5 The current density-voltage (JV) curve was displayed. By testing the photoelectric performance of cesium-based perovskite solar cells, it was found that the cesium-based perovskite film Al2O3 / PTAA / Cs x (CH3NH3) 1-x The PbI3-structured device exhibited an encouraging photoelectric conversion efficiency (PCE) of 17.85%. XRD, SEM, and JV results confirmed that the high crystalline quality and uniform surface morphology of the cesium-based perovskite film are key factors in achieving high-efficiency optoelectronic device performance.
[0065] Example 2: Cesium-based perovskite Cs x (CH3NH3) 1-x Precursor solution of PbI3 (x is about 0.012), thin film and high-efficiency perovskite solar cells
[0066] Precursor solution preparation
[0067] 1. First precursor solution:
[0068] Weigh CsI and PbI2 powders in dry air and add them to a mixture of NMP and DMSO (5:1 by volume) that has been pre-oxidized for 8 hours to a concentration of 1 M. Once fully dissolved, filter with an organic filter to remove impurities.
[0069] 2. Second precursor solution:
[0070] Under nitrogen, weigh CH3NH3I and PbI2 powders (molar ratio 1:4) and dissolve them in a DMF:DMSO (500:40) mixture to a concentration of 556 mg / ml. Once fully dissolved, filter the mixture through an organic filter to remove impurities and allow to stand.
[0071] 3. The third precursor solution:
[0072] The first precursor solution and the second precursor solution were mixed at a volume ratio of 15:1000, stirred for 20 minutes, and allowed to stand for 10 minutes.
[0073] Preparation of cesium-based perovskite thin films
[0074] 1. Dissolve CH3NH3I in isopropanol (40 mg / ml) to form a fourth precursor solution.
[0075] 2. Spin-coat the third precursor solution onto the ITO substrate at a first speed of 7000 rpm for 30 seconds, a second speed of 4000 rpm for 30 seconds, and vertically add the fourth solution at the 30th second before the end. Anneal at 100°C for 35 minutes.
[0076] Preparation of cesium-based perovskite solar cells
[0077] The structure is ITO / Al2O3 / PTAA / cesium-based perovskite film / PEAI / PCBM / BCP / Ag.
[0078] The photoelectric conversion efficiency of cesium-based perovskite solar cells is 15.38%.
[0079] Example 3: Cesium-based perovskite Cs x (CH3NH3) 1-x PbI3 (x is about 0.018) precursor solution, film and perovskite solar cell
[0080] Precursor solution preparation
[0081] 1. First precursor solution:
[0082] Weigh CsI and PbI2 powders in dry air and add them to a mixture of NMP and DMSO (5:1 by volume) that had been pre-oxidized for 7 hours to a concentration of 1 M. Filter through an organic filter to remove impurities.
[0083] 2. Second precursor solution:
[0084] Under nitrogen, weigh CH3NH3I and PbI2 powders (molar ratio 1:4) and dissolve them in a DMF:DMSO (500:40) mixture to a concentration of 556 mg / ml. After dissolution, filter the mixture through an organic filter and allow to stand.
[0085] 3. The third precursor solution:
[0086] The first precursor solution and the second precursor solution were mixed at a volume ratio of 22.5:1000, stirred for 30 minutes, and allowed to stand for 15 minutes.
[0087] Preparation of cesium-based perovskite thin films
[0088] 1. Dissolve CH3NH3I in isopropanol (40 mg / ml) to form a fourth solution.
[0089] 2. Spin-coat the third solution onto the ITO substrate at a first speed of 6050 rpm for 30 seconds, a second speed of 4050 rpm for 30 seconds, and vertically add the fourth solution dropwise at the 30-second mark. Anneal at 100°C for 40 minutes.
[0090] Preparation of cesium-based perovskite solar cells
[0091] The structure is ITO / Al2O3 / PTAA / cesium-based perovskite film / PEAI / PCBM / BCP / Ag. The photoelectric conversion efficiency of the cesium-based perovskite solar cell is 16.48%.
Claims
1. A method for preparing a cesium-based perovskite solution, characterized in that: The steps include: (1) Using a balance, weigh the cesium salt and metal halide powders separately and then mix them to form a precursor powder; (2) adding the first organic solvent to the mixture precursor powder of step (1), stirring the mixture with a magnetic stirrer for 6-8 hours until the mixture is completely dissolved to form a first precursor solution; (3) Weighing the organic halide and the metal halide separately using a balance, and then mixing them into a precursor powder; (4) adding a second organic solvent to the mixture of step (3) and stirring with a magnetic stirrer until the mixture is completely dissolved to form a second precursor solution; (5) filtering the first precursor solution and the second precursor solution in steps (2) and (4) respectively using an organic filter to remove insoluble impurities; (6) Using a pipette, the first and second precursor solutions filtered in step (5) are extracted respectively in a certain volume ratio and mixed to form a third precursor solution, i.e., a cesium-based perovskite solution.
2. The preparation method according to claim 1, characterized in that The cesium salt described in step (1) is one or more of cesium chloride, cesium bromide, cesium iodide, and cesium carbonate. The metal halide is one or more of lead chloride, lead bromide, and lead iodide. The first organic solvent described in step (2) is a mixture of N-methylpyrrolidone and dimethyl sulfoxide. The organic halide described in step (3) is one or more of methylamine chloride, methylamine bromide, and methylamine iodide. The metal halide is one or more of lead chloride, lead bromide, and lead iodide. The second organic solvent described in step (4) is a mixture of N,N-dimethylformamide and dimethyl sulfoxide.
3. The preparation method according to claim 2, characterized in that N-methylpyrrolidone, one of the first organic solvents, is oxidized in air for 5-8 hours.
4. The preparation method according to claim 2, characterized in that The volume ratio of the first organic solvent, N-methylpyrrolidone, to dimethyl sulfoxide is (5:1)-(3:1). The volume ratio of the second organic solvent, N,N-dimethylformamide, to dimethyl sulfoxide is (90-105):(1-10).
5. The preparation method according to claim 1, characterized in that The concentration of the first precursor in step (2) is 1 M to 2 M. The concentration of the second precursor in step (4) is 460 mg / ml to 700 mg / ml.
6. The preparation method according to claim 1, characterized in that The molar ratio of the cesium salt to the metal halide in step (1) is 1:
1. The molar ratio of the organic halide to the metal halide in step (3) is 1:4 to 1:
3.
7. The preparation method according to claim 1, characterized in that The volume ratio of the first precursor solution to the second precursor solution in step (6) is (10-100):(800-1200).
8. The preparation method according to claim 1, characterized in that The solid powders of cesium salts and metal halides were weighed in dry air, and the organic halides were weighed in a nitrogen environment.
9. A novel two-step interdiffusion method for preparing cesium-based perovskite thin films, characterized in that: The steps include: (1) adding an organic halide to a third organic solvent, stirring until completely dissolved, filtering with an organic filter head, and allowing to stand to form a fourth precursor solution; (2) depositing the third precursor mixed solution according to claim 1 on the surface of the substrate, and vertically interposing the fourth organic halide precursor solution during the spin coating crystallization formation stage to form a cesium-based perovskite wet film; (3) Annealing the cesium-based perovskite wet film at a temperature of 50 to 150° C. for 10 to 60 minutes to obtain a high-quality cesium-based perovskite film with good crystallization state.
10. The preparation method according to claim 9, characterized in that The organic solvent in step (1) is isopropanol, and the concentration of the fourth precursor solution is 20 mg / ml-80 mg / ml.
11. The preparation method according to claim 9, characterized in that In step (2), the wet film is deposited by spin coating, the first spin coating speed is 6000-8000 rpm, the spin coating time is 20-60 seconds, the second spin coating speed is 4000-5999 rpm, and the spin coating time is 40-60 seconds.
12. The preparation method according to claim 9, characterized in that: The time for vertical intervention of the fourth precursor solution in step (2) is 10-40 seconds in reverse.
13. A method for preparing a cesium-based inverted pure iodine perovskite solar cell device, characterized in that: The invention comprises transparent conductive glass, a modified layer or no modified layer, a hole transport layer, a cesium-based perovskite thin film layer prepared by the method according to claims 9 to 12, a modified layer or no modified layer, an electron transport layer, a passivation layer, and a metal electrode. The electron transport layer is one of TiO2, SnO2, PCBM, or ZnO, and has a thickness of 10 to 100 nm; the hole transport layer is one of Spiro-OMeTAD, PTAA, or NiOx, and has a thickness of 5 to 150 nm.